"Mycenaean culture" - On the history of the concept of "Mycenaean culture" in the 19th century and on the concepts of "culture" and "civilization" in Heinrich Schliemann's book publications .,Mykenische Kultur" - zur Geschichte des Konzepts .,mykenische Kulturv im 19. Jahrhundert und zum .,Cultur"- und .,Civilisations"-Begriff in den Buchpublikationen Heinrich Schliemanns - Mühlenbruch, Tobias (Praehistorische Zeitschrift, 2024)
Based on the 19th century publications evaluated in this article, "Mycenaean"features and objects were first linked to the concept of "civilisation"by H. Schliemann in 1878 and subsequently, in 1879, to a specific "culture"or "civilisation"by both A. Furtwängler and G. Loeschcke, and F. Lenormant. In 1883, A. Milchhöfer introduced the term "mykenische Cultur", which Schliemann used only in his last excavation report on Troy, published in 1891. Before that, in 1886, Furtwängler and Loeschcke had used the terms "mykenischer Culturkreis"and "mykenischer Kreis", and they had also written of a "mykenisches Reich". In the same year, in his excavation report on Tiryns, Schliemann had still used the formulation "tirynthische und mykenische Civilisation". In the archaeological publications considered here, the terms "culture"and "civilisation"were not explicitly defined. With regard to the use of the terms "culture"and "civilisation"both by Schliemann and by the colleagues who contributed to his books or who were cited by him, it is noticeable that both terms were apparently understood at least on the whole synonymously. An evaluation of the "height of culture"or "height of civilisation"can be found in passages by Schliemann and his colleagues, and in each case evolutionist ideas can be identified.
CRIS-Team Scopus Importer:2024-06-28
Keywords: archaeological concept of "culture"; Bronze Age Troy; Heinrich Schliemann; History of research on the Aegean Bronze Age; Mycenaean Greece